PENGARUH MODEL PEMBELAJARAN CIRCUIT LEARNING TERHADAP KETERAMPILAN MENULIS NASKAH DRAMA SISWA KELAS VIII SMPN 35 MEDAN - Yohana Hartati Sianipar; Syairal Fahmy Dalimunthe (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to determine the drama script writing abilities of SMPN 35 Medan class VIII students using both conventional direct instruction learning models, circuit learning models, and knowing the effect of differences in the use of direct instruction learning models and circuit learning models on the drama script writing skills of class VIII students at SMPN 35 Medan. The two-group post-test design experiment approach was employed in this study. Only SMPN 35 Medan class VIII pupils made up the study's population. For the 2023–2024 academic year, SMPN 35 Medan will have 256 class VIII students spread over 8 classes. The research sample consisted of 32 students from class VIII-5 which was the experiment class and 32 students from class VIII-7 which was the control class, out of the 256 students. Interviews, observation, and objective description exams were used as study instruments. The average score for students in the experimental class who wrote drama scripts was 81.44, falling into the good category, according to the research results. In contrast, students in the control class scored an average of 57.06, falling into the adequate category but still failing to meet the Minimum Completeness Criteria (KKM) namely 75. The significance level settings of α= 0.05 and n= 32 yielded ttable= 2.039 based on the t test. The alternative hypothesis Ha is accepted and the null hypothesis H0 is rejected if it can be shown that tcount > ttable, that is, 10.174>2.039. This demonstrates that the writing skills of class VIII students at SMPN 35 Medan for drama scripts fluctuate significantly depending on whether the direct instruction learning model or the circuit learning model is used. This indicates that class VIII students at SMPN 35 Medan are more influenced by circuit learning models when it comes to their ability to write drama scripts.